engaruh Dosis Pupuk NPK dan Ordo Tanah terhadap Kdd, Serapan K, dan Hasil Bibit Kentang (Solanum tuberosum L.) yang Diinokulasi Fungi Mikoriza Arbuskula dan Mycorrhiza Helper Bacteria - Windy Amorita; Anne Nurbaity; Diyan Herdiyantoro (Fakultas Pertanian Universitas Padjadjaran, 2016)
The productivity of potatoes in Indonesia is relatively low and unstable caused by unsuitable enviromental and soil conditions and bad cultivation system. This research was conducted to study the effect of NPK fertilizer dosages and soil order to soluble K, K Uptake, and yield of seed potatoes (Solanum tuberosum L.). The experiment design used a factorial randomized block design with two factors and three replication. The first factor was NPK fertilizer dosages with five levels (0, 25, 50, 75, 100% recomendation dosages) and the second factor was soil orders with two levels (Andisols and Inceptisols). The results of experiment showed that the interaction effect between NPK fertilizer dosages and soil orders had significantly effect to soluble K and K Uptake. There were independent effect of NPK dosages to diameter of potatoes tuber and independent effect of soils order to yield of seed potatoes. Andisols with 25% NPK and Inceptisols with 50% NPK were the best combination treatment to increase soluble K while treatment Inceptisols with 25% NPK was the best combination treatment to increase K Uptake. Dosages of 25% NPK was the best treatment to increase diameter of potatoes tuber while Inceptisols was the best treatment to increase yield of seed potatoes.Keywords : NPK Fertilizer Dosages, Andisols, Inceptisols, Potassium, Potatoes